Malaysian teachers network portal. - Abdul Hamid, Mohd Naim; Othman, Roslina (IIUM Press, 2011)
The system is for l'vlalaysian teachers who are in primary and secondary schools. Some teacher professional organizations have existed but they do not have the opportunity to participate or collaborate online through WWW (the Internet). Online or electronic collaboration & knowledge sharing among teachers in Malaysia is a new phenomenon. But with the advance of the Internet utilization and the availability of the Internet by more then 80% of school in Malaysia, the teacher should be given the opportunity to explore the possibility of online communication to collaborate & share their knowledge and teaching resources. The project is part of an outsource electronic teachers knowledge portal of a PhD research work at KICT. The system is developed using PHP language and MYSQL for the database